Influence of Nutritional Flushing Prior to Mating on the Performance of West African Dwarf Goats Mated in the Rainy Season - Karikari, P.K.; Blasu, E.Y. (Pakistan Journal of Nutrition, 2009)
The effect of nutritional flushing for a period of six weeks prior to mating on the physical condition, serum metabolic and hormonal status at mating and litter size at birth of 32 pluriparous West African Dwarf (WAD) goats was studied using a 2 x 2 factorial design. The factors in the design were age (young, 3-4 years old versus old, 5-6 years old) and nutritional flushing regime (pasture alone versus pasture plus concentrate supplementation). The young does gained more weight and body condition (2.0±0.30 kg; 0.53±0.10 units; p>0.05) over the 6-wk nutritional flushing period than the old does (1.4±0.30 kg; 0.40±0.10 units), but the old does were heavier (p0.05) between treatments. The serum glucose concentrations were also similar for the treatment groups and averaged 2.6±0.10 mmol/l at mating. At the end of the nutritional flushing period, supplemented does had a higher (p